The influence of connotation ideology on audience cognition in games - Yan, Wang; Rungsrisawat, Somdech (Edelweiss Applied Science and Technology, 2025)
This study examines how ideological content in electronic games influences player cognition and behavior, combining quantitative surveys (N=484) and qualitative interviews (n=8) within China’s gaming ecosystem. The research aims to (1) assess players’ recognition of ideological content, (2) analyze behavioral and attitudinal changes, and (3) evaluate how media dissemination channels moderate these effects. Methodologically, the study employs an exploratory sequential mixed-methods design, integrating validated psychometric scales (Content Sensitivity, Subjective Sensitivity, Behavioral Sensitivity, Environmental Sensitivity) with thematic analysis of industry expert interviews. Quantitative results reveal significant positive correlations between content exposure and cognitive/behavioral outcomes, with environmental factors (social media) amplifying ideological reception. Qualitative findings demonstrate that players actively reinterpret cultural narratives through participatory practices, though platform algorithms and policy constraints shape these processes. The study contributes novel theoretical frameworks: ludic social capital (stratified in-game status systems) and regulatory prototyping (policy-driven innovation constraints). Key conclusions highlight the dialectical nature of game-based ideological influence where designer intent, player agency, and platform architectures interact dynamically.